The effect of diluted ropivacaine in distending fluid on cramping pain after hysteroscopic surgeries: a randomized clinical trial study - Kobra Tahermanesh; Abolfazl Mehdizadeh Kashi; Marziyeh Ajdary; Samaneh Rokhgireh; Masood Mohseni; Shahla Chaichian; Maryam Ahmadi (Korean Society of Obstetrics and Gynecology, 2022)
Objective The effect of ropivacaine on postoperative hysteroscopy has not yet been evaluated; this study investigated the effect of diluted ropivacaine in distending media during hysteroscopy on postoperative cramping pain. Methods This double-blind randomized clinical trial was conducted on 60 women who underwent hysteroscopy at a tertiary hospital. Normal saline was used as the distending fluid in both groups. The intervention group received 10 mL of 2% ropivacaine in only one bottle of 1,000 mL normal saline as a distending fluid, while the control group received 10 mL of normal saline in 1,000 mL normal saline during hysteroscopy. Patients' pain scores were evaluated before hysteroscopy and at 2, 6, 12, 24, and 48 hours after hysteroscopy. Results Based on the results, the pain measured by visual analog scale (VAS) score was significant at 6 and 12 hours after the intervention was significantly lower than that in the ropivacaine group (3.03±1.57 vs. 4±1.49, P=0.02 at 6 hours and 1.28±1.36 vs. 2.4±1.43, P=0.003 at 12 hours). There were no significant differences in the VAS scores at 2, 24, and 48 hours after the intervention between the two groups. Conclusion Ropivacaine in the distending fluid during hysteroscopy is associated with a significant reduction in pain within a few hours after hysteroscopy with no remarkable adverse effects.